Care Management and Cost Control in Pediatric Accountable Care Organizations: A Comparative Case Study - Ann Scheck McAlearney; Jennifer L. Hefner; Rajitha D. Venkatesh; Daniel M. Walker (Health Economics and Management Review, 2025)
As accountable care organizations have proliferated across the healthcare landscape, research into the factors contributing to accountable care organization development for adults has identified useful approaches to managing care under this care model. Yet, investigation into pediatric accountable care organizations is lacking, leaving policy-makers and pediatric accountable care organization administrators unable to better address the unique challenges of caring for children. To address this gap and identify differences between accountable care organizations serving these two populations, two pediatric and two adult accountable care organizations operating in the private sector were compared in this study. A comparative case study design consisting of two site visits to each of the accountable care organizations was used to conduct this research. The four accountable care organizations included in this study were purposely selected to provide geographic and population diversity. Site visits were conducted in Columbus, Ohio, USA, Kansas City, Missouri, USA, Golden Colorado, USA, and Chicago, Illinois, USA from 2013 to 2014. The case studies consisted of 89 key informant interviews performed during site visits to each of the organizations, supplemented by document collection and follow-up telephone interviews. All interviews were analyzed via both inductive and deductive methods to identify differences between the pediatric and adult accountable care organizations. For this comparative analysis, the aim was to study both pediatric and adult accountable care organizations to identify differences in accountable care organization development and management practices that may exist, focusing in particular on process aspects that might vary. Our study found that pediatric accountable care organizations have unique approaches to care management and cost control. Specifically, there were four key differences identified between the types of accountable care organizations: 1) the role of primary care; 2) the challenge of cost control; 3) the importance of scale; and 4) approaches to measurement. These findings can help better focus efforts to implement and standardize the accountable care organization model to meet needs of the pediatric population. Future research should be undertaken to further understand the circumstances and goals of pediatric ACOs.